Studi Etnomatematika: Aktivitas Petani Padi Dusun Panggang - Firdaus, Bara Aji; Widodo, Sri Adi; Taufiq, Irham; Irfan, Muhammad (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study explores the hidden mathematical concept of the activities of the rice farmers in Panggang Village. The research method is qualitative research with an ethnographic approach. The research location is in Panggang Hamlet, Bantul. The location was chosen because the area is an agricultural area that has been regulated by the Government. The research subjects were the Dukuh and Panggang Dusun farmers and were selected purposively. Agricultural activities contain mathematical concepts that arise when using rice seeds, nursery preparation, fertilizing, and tandur. This study's findings are that there are mathematical concepts that exist in agricultural activities, including geometry and comparisons. The results of the research can be used as teaching materials to facilitate learning for students.Keywords: ethnomathematics, geometry, comparison, contextual, realistic mathematics education